A TOA-AOA-Based NLOS Error Mitigation Method for Location Estimation. (2008) - Tang Tang, Hong Hong; Park Park, Yongwan Yongwan; Qiu Qiu, Tianshuang Tianshuang
Abstract : This paper proposes a geometric method to locate a mobile station (MS) in a mobile cellular network when both the range and angle measurements are corrupted by non-line-of-sight (NLOS) errors. The MS location is restricted to an enclosed region by geometric constraints from the temporal-spatial characteristics of the radio propagation channel. A closed-form equation of the MS position, time of arrival (TOA), angle of arrival (AOA), and angle spread is provided. The solution space of the equation is very large because the angle spreads are random variables in nature. A constrained objective function is constructed to further limit the MS position. A Lagrange multiplier-based solution and a numerical solution are proposed to resolve the MS position. The estimation quality of the estimator in term of "biased" or "unbiased" is discussed. The scale factors, which may be used to evaluate NLOS propagation level, can be estimated by the proposed method. AOA seen at base stations may be corrected to some degree. The performance comparisons among the proposed method and other hybrid location methods are investigated on different NLOS error models and with two scenarios of cell layout. It is found that the proposed method can deal with NLOS error effectively, and it is attractive for location estimation in cellular networks.